Difference in Biochemical Composition and Nutritional Trait in Different Areas of Fillets of Dorsal, Venter-cha, and Ventral of Carangoides fulvoguttatus - Aberoumand, Ali; Fardaei, Fatemeh (Journal of Agri-Food Science and Technology, 2025)
Environmental parameters are essential to the life cycle and physiological activities of fish. These environmental conditions can profoundly influence fish physiology, behavior, and their nutrition. The purpose of this study was to highlight nutritional properties of dorsal, ventercha and ventral fillets from sea fish Carangoides fulvoguttatus. Dorsal, ventercha and ventral fillet portions of Iranian sea fish (C. fulvoguttatus) analyzed for proximate constituents, energy values and pH. The proximate of C. fulvoguttatus fillets varied between three anatomical locations ventercha, dorsal and ventral. Moisture and fat content differentiated dorsal and ventercha from ventral in fish muscle. In particular, a relatively large variation observed in crude fat content, which trend of significant fat changes between the three portions was as follows: ventral>ventercha>dorsal. The results showed that the ventral part containing significantly less moisture (73.4%±0.7), but the ventercha part had protein content (15.7%±0.3) which was higher than the other two parts of muscle. The ventral part had higher fat content (7.13%±0.1). The energy value (127.08 kcal/100 g) in ventral part found the highest. The ventercha area containing highest protein content and ventral had highest lipid content (7.13%). The index of nutritional quality for protein was always higher in ventercha than in dorsal and ventral, that of fish being especially interesting because it is associated with a relatively lower energy value. The nutritional traits found best in ventral muscle due to highest dry matter and energy value with lowest moisture.